CHRISTIAN BURIAL GROUNDS OF UPLAND DAGESTAN (BASED ON THE JOINT DAGESTAN-GEORGIAN ARCHEOLOGICAL EXPEDITION) - Gambasidze, Givi Gajozovic; Abiev, Askerhan Kamalovic (History, Archeology and Ethnography of the Caucasus, 2020)
The paper proposes material of the study of medieval burial grounds of upland Dagestan, obtained during the joint Dagestan-Georgian archeological expedition, which was carried out in Central Upland Dagestan, in the territory of the former Sarir, in 1977-1981. As a result of a comprehensive work, in addition to archeological, architectural, ethnographic and epigraphic monuments, the following medieval burial grounds were studied: Tad-raal, Akhalchinsky, Uradinsky, Khunzakhsky. These burial grounds have been identified with burials dating back to the X-XIV centuries, as well as one burial belonging to the XIX century. Identified medieval burials comprise three types of burial structures: 1) burials in ground pits of rectangular elongated shape; 2) burials in rectangular stone boxes; 3) burials in soil pits of elongated rectangular shape with ledges-shoulders and slabs of horizontal overlaps. The Tad-raal burial of XIX century was made in a wood coffin.The article provides a detailed description of the revealed burial complexes, characterizes the construction of their structures, funeral rite, funeral set and dating of burials. Using the method of comparative analysis of structural features of burial structures and equipment, the dating of the functioning of burial grounds is specified. The considered material allows to conclude on active historical ties of mountain Dagestan with medieval Georgia, as well as the spread of Christianity among the local population. At the same time, it is noted that the expressive and peculiar local culture has preserved the features of the previous epoch, which is reflected in the funeral rite and funeral structures.
Keywords: Mountain Dagestan; Georgia; burial grounds; burial structures; funeral rite; middle ages; Christianity.